DISKURSUS KERUKUNAN SOSIAL DALAM PERSPEKTIF MASYARAKAT KRISTEN DI INDONESIA: - Yudhi Kawangung; Jeni Ishak Lele (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
After the 2019 National Election in Indonesia, which still left problems both essentialism and mechanism, this nation has been materially and immaterially drained. Later, the political elites who benefit the situation for their interest have been very annoying and disturbing. Therefore, the harmony among the religious people in Indonesia is triggered by differences in political views, even having to reduce religious narratives and diction which are then forced even if they are contrary to human values. As a result, the discourse of social harmony is initiated by the community figures through no-theme participation; it becomes a formula that must be immediately implemented in such way that the unity of the nation might be restored after having been torn apart by the different political view. The discourse of social harmony might be attached to the Christian perspective that offers a completely new idea in accordance to the context of the problems in Indonesia. Through the literacy method, the form of re-reading and re-checking the diction and the narration have been formulated and provided new meaning or discourse into the social harmony of the digital-era Indonesian people altogether. It might be concluded that holding no-theme participation with literacy skills mastery is important to conduct among the digital-era Indonesian people since the digital era itself might be considered as one of the contributing factors to the present problems (such as hoax, deception and hate speech) that have so widely spread that they start to erode the unity and the integrity of Indonesia.